Kepemimpinan Gembala Sidang dan Dampaknya terhadap Sekolah Minggu Dewasa: Studi Kasus Gereja Baptis Indonesia di Kota Kediri - Jemmy, Jemmy; Effendi, Daniel Tatang (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2025)
Significant variability in the spiritual impact and congregational engagement in Adult Sunday School (SMD) programs of Union of Indonesia Baptist Church (GGBI) in Kediri City indicates uneven program effectiveness, strongly suspected to result from differences in pastoral leadership. This study aims to analyze the role and impact of such leadership on SMD effectiveness, identify crucial factors, and formulate strategies for its improvement. Employing a qualitatively dominant mixed-methods approach (QUAL+quan) with 8 pastors and 24 participants, positive correlations were found between leadership effectiveness and formal qualifications (r=0.65−0.78) as well as experience (r=0.63−0.69). Transformational and pastoral leadership styles were found to be significantly more effective in enhancing SMD quality compared to administrative styles. The SMD programs also demonstrated notable enhancements in spiritual, social, and learning dimensions. These findings recommend an Integrative and Contextual Pastoral Leadership Model—synergizing transformative vision, pastoral guidance, supportive governance, and adaptability—as a strategic solution for enhancing SMD effectiveness.AbstrakVariabilitas signifikan dampak spiritual dan keterlibatan jemaat pada Sekolah Minggu Dewasa (SMD) Gereja Baptis Indonesia (GBI) Kota Kediri mengindikasikan efektivitas program yang belum merata, diduga kuat akibat perbedaan kepemimpinan gembala sidang. Penelitian ini bertujuan menganalisis peran dan dampak kepemimpinan tersebut terhadap efektivitas SMD, mengidentifikasi faktor krusial, serta merumuskan strategi peningkatannya. Menggunakan pendekatan mixed method dominan kualitatif (QUAL+quan) pada 8 gembala dan 24 peserta, ditemukan korelasi positif antara efektivitas kepemimpinan dengan kualifikasi formal (r=0.65−0.78) dan pengalaman (r=0.63−0.69). Gaya kepemimpinan transformasional dan pastoral terbukti signifikan lebih efektif meningkatkan kualitas SMD dibanding gaya administratif. Program SMD juga menunjukkan peningkatan nyata pada dimensi spiritual, sosial, dan pembelajaran. Temuan ini merekomendasikan Model Kepemimpinan Gembala Sidang Integratif dan Kontekstual mensinergikan visi transformatif, pendampingan pastoral, tata kelola suportif, dan adaptabilitas—sebagai solusi strategis peningkatan efektivitas SMD.